Study on the Interactions Process of Coupled Model of Furrow Opener–Soil–Pot Seedling Based on Discrete Approach - Bin Jiang; Jinping Cai; Xiongfei Chen; Junan Liu; Liping Xiao; Jinlong Lin; Yuqiang Chen (Agriculture)
The upright state of pot seedlings in the process of rice mechanized throwing operations has an important influence on the growth rate and yield of rice, and pot seedling uprightness is affected by the influence of soil backfilling during trenching. Due to the complexity of the furrow opener–soil–pot seedling interaction mechanism in the rice pot seedling planting process, the soil backfilling process is difficult to observe. In order to improve the uprightness of pot seedling planting, this paper constructs a soil model and a soil–pot seedling model step by step, based on the discrete element method (DEM), as well as a coupled model of the pot seedling planting system to study the process of furrow opener–soil–pot seedling planting, the reliability of which is then verified. The results showed that the simulation results of the constructed soil model and soil–pot seedling model deviated from the actual calibration results by <6%, and the model could accurately simulate the pot seedling throwing process. The simulation analysis of the trenching process revealed that the soil backfilling process during trenching showed a three-stage evolution pattern of “backfilling-covering-stabilizing”; in addition, the forward speed of the machine was 0.8 m/s, and the falling speed of the seedling discharge cylinder was 3.5 m/s, which made it possible for the model to simulate the pot seedling throwing process accurately. In addition, when the pot seedling with a forward speed of 0.8 m/s and a drop speed of 3.5 m/s fell into the trench after 0.15 s of trenching, its lateral and longitudinal uprightness were 67.0 ± 1.2° and 65.2 ± 1.5°, respectively. After optimization of the structure of the trenchers, the width, depth, and length of the main body were 40 mm, 37.87 mm, and 32.32 mm, respectively, and the lateral and longitudinal uprightness of the pot seedlings increased to 70.0 ± 1.0° and 69.4 ± 0.8, respectively. The coupled model bench validation test showed that its reliability error was <5%. The coupled model provides technical support for the design and parameter optimization of rice planting equipment.